Yield of adenomas and colorectal cancers within 5 years of a negative colonoscopy: are the guidelines guiding?. Issue 1 (14th June 2016) - Tee, Chin Li; Stephensen, Bree; Sloss, Andrew; Grieve, David A.
Abstract : Background: Screening for colorectal cancers outside the recommended guidelines presents a considerable burden to resource management in many public hospitals. The aim of this study is to evaluate the frequency, indications and outcomes for repeat colonoscopy performed within 5 years of a negative colonoscopy. Methods: A retrospective review of all colonoscopies at Nambour Hospital in 2008 was performed to identify those with a negative colonoscopy. The charts of patients undergoing repeat colonoscopy at the same institution within 5 years of a negative colonoscopy were examined further, and data obtained regarding indications and outcomes of subsequent colonoscopies. Results: A total of 616 colonoscopies were identified, 427 (69.3%) were negative for adenoma and carcinoma. Of these patients, 74 (17.3%) underwent a repeat colonoscopy at Nambour Hospital within 5 years. Eighteen out of 74 (24.3%) were outside guideline recommendation. Overall, one patient (1.4%) had cancer and 11 patients (14.9%) had polyps detected at repeat colonoscopy. Most of the polyps detected had low‐risk features and were detected in the fourth and fifth years of the study period. Conclusion: The yield of a second colonoscopy within 5 years of a good‐quality negative colonoscopy is low but not zero. In the absence of new concerning symptoms or other risk factors, patients can be reassured and guidelines adhered to.